2009
DOI: 10.1177/0363546508328105
|View full text |Cite
|
Sign up to set email alerts
|

Biceps Activity during Windmill Softball Pitching

Abstract: Repetitive eccentric biceps contractions may help explain the high incidence of anterior shoulder pain clinically observed in elite windmill pitchers. Injury prevention and treatment mechanisms should focus on the phases with the highest muscle activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 14 publications
2
43
1
Order By: Relevance
“…The pitching surface was positioned so that the participant's stride foot would land on top of a 40 6 60 cm Bertec force plate (Bertec Corp, Columbus, OH), which was anchored into the floor. For the current study, those data from the fastest pitch passing through the strikezone were selected for detailed analysis (Guido et al, 2009;Oliver & Keeley, 2010a, 2010bRojas et al, 2009). Pitch velocity was determined by a JUGS radar gun (OpticsPlanet, Inc., Northbrook, IL) positioned at the base of the pitching surface and directed towards home plate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pitching surface was positioned so that the participant's stride foot would land on top of a 40 6 60 cm Bertec force plate (Bertec Corp, Columbus, OH), which was anchored into the floor. For the current study, those data from the fastest pitch passing through the strikezone were selected for detailed analysis (Guido et al, 2009;Oliver & Keeley, 2010a, 2010bRojas et al, 2009). Pitch velocity was determined by a JUGS radar gun (OpticsPlanet, Inc., Northbrook, IL) positioned at the base of the pitching surface and directed towards home plate.…”
Section: Methodsmentioning
confidence: 99%
“…The sport of fast-pitch softball has become very popular for female athletes and is a unique athletic skill that is beginning to be explored (Barrentine, Fleisig, Whiteside, Escamilla, & Andrews, 1998;Guido, Werner, & Meister, 2009;Oliver, Dwelly, & Kwon, 2010;Rojas et al, 2009;Werner et al, 2005;Werner, Jones, Guido, & Brunet, 2006). It has been reported that during 2003 more than 2 million girls participated in the sport of softball (Werner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The peak of activation is shortly before ball release. Here, the elbow is flexed minimally and the biceps is contracted eccentrically (28,30).…”
Section: Pitchingmentioning
confidence: 99%
“…Since the overhand throwing technique is identical in baseball and softball, rotator cuff problems such as tendinitis, strains, and impingement are still commonplace. However windmill pitchers seem to be at increased risk of developing biceps tendinitis due to the high levels of biceps brachii muscle activation that occurs near the end of the delivery (28,30). Athletes will complain of pain through the bicipital groove in the anterior aspect of the proximal humerus.…”
Section: Proximal Biceps Tendinitismentioning
confidence: 99%
“…The biomechanics of windmill softball pitching remains scantly investigated relative to overhand throwing, and some investigators have reported commonalities between the two forms of throwing in terms of kinetics and relative risk for injuries of the pitching arm (1, 15, 24, 39, 40). However, there are obvious kinematic differences between windmill and overhand throwing which likely influence where internal loads are placed and resultant tissue adaptation.…”
Section: Discussionmentioning
confidence: 99%